THE ROLE OF SCHOOL PRINCIPALS IN IMPROVING THE QUALITY OF EDUCATION BASED ON NATIONAL EDUCATION STANDARDS AT SD NEGERI 1 KUALASIMPANG - Wulandari, Wulandari; Husin, M.; Sulaiman, Sulaiman (Universitas Syiah Kuala, 2024)
The problem formulation in this research is about the role of the principal in improving the quality of education based on national education standards at SD Negeri 1 Kualasimpang. This research aims to determine the role of the Principal in order to improve the quality of education at SD Negeri 1 Kualasimpang and can serve as a guide for other school principals. The research design used was descriptive qualitative. Using interview sheets with 3 sources, namely the principal, teachers and school operators, as well as observation sheets used to find out school facilities and infrastructure. From the research results it can be concluded that in improving the quality of education the school principal carries out his role as 1) educator, the school principal creates a conducive work climate and provides advice. 2) managers, school principals plan quality education programs, prepare and make school plans, and lead schools, 3) administrators, school principals manage finances, plan the curriculum, and manage facilities and infrastructure, 4) supervisors, school principals plan, implement, and realizing educational supervision, as well as supervising the work carried out by educational staff, 5) leaders, school principals know the school's vision and mission, and the ability to make decisions, 6) innovators, school principals establish harmonious relationships with the surrounding community, and become role models for the school community , 7) motivator, the school principal provides sanctions according to existing regulations, and regulates the implementation of an adequate work atmosphere. Based on the results of interviews, observations and documentation obtained, the school principal can be said to have carried out his role well.